A New Simplified Onlay Technique for Posterior Cruciate Ligament Reconstruction - Salim, Rodrigo; Fogagnolo, Fabricio; Kfuri, Mauricio, Jr. (The Journal of Knee Surgery, 2014)
The integrity of posterior cruciate ligament (PCL) is essential for the normal kinematics of the knee. Injury to the PCL has adverse consequences, with worsening of functional performance and an increased risk to develop osteoarthritis. Conservative treatment is sometimes adopted, not only because it is an acceptable option for selected patients but also due to the lack of consensus in the orthopedic literature regarding the best surgical method. Hereby we describe a simplified technique for onlay PCL reconstruction pointing out possible advantages if compared with the traditional transtibial or inlay techniques.
Keywords: cruciate ligament; ligament reconstruction; technique